Almost everywhere convergence of varying parameter setting Cesàro means of Fourier series with respect to Walsh-Kaczmarz-system - Adimasu, Anteneh Tilahun (Annales Mathematicae Silesianae, 2025)
In this paper, the almost everywhere convergence of Cesàro means of Walsh–Kaczmarz–Fourier series in a varying parameter setting is investigated. In particular, we define subsequence ℕα_n,q of natural numbers and prove that the maximal operator sup_n∈ℕα_n,q|σnα_nf| is of strong type (H1,L1), where H1 is a Hardy space.